Evaluation of Egg Quality During Post Storage Soiling in Gelatin Extract from Bali Cattle Skin - D. B. A., Ginting; Miwada, I N. S.; Lindawati, S. A. (Jurnal Peternakan Tropika; Vol 6 No 3 (2018), 2018)
This study aims to evaluate the potential of gelatin extract from bali cowhide in maintaining the quality of duck eggs and determine the response of panelists to the quality of post-soaking gelatin extract eggs. This research has been carried out at the Animal Husbandry and Microbiology Technology Laboratory, Faculty of Animal Husbandry, Udayana University. This study lasted for one month from May 4 to June 4, 2018. The design used was a Completely Randomized Design (CRD) with five treatments and three repetitions. The treatments were without soaking or control (P0) soaking gelatin for 15 minutes (P15) soaking gelatin for 30 minutes (P30) soaking gelatin for 45 minutes (P45) and soaking gelatin for 60 minutes (P60). The variables observed were egg white index, egg yolk index, egg yolk color, egg aroma and egg flavor. The results showed that there was an influence between the length of the duck egg immersion and the control or not given the gelatin soaking of bali cowhide on the panelist's preference for the color of yolk, flavor and aroma was significantly different (P <0.05) this was due to the alleged gelatin immersion to maintain and the penetration of gelatin protein with protein in eggs and can maintain the decomposition of fat and carbohydrates in duck eggs while the yolk index and egg white index have no significant effect (P> 0.05) this is due to the high molecule in gelatin which is in the range 67-167 kilodalton so that the penetration of gelatin in covering the pores of egg shells is not optimal and the occurrence of gelatin clotting occurs during storage which has an unreal effect. Based on the results of the study that the administration of gelatin solution from bali cowhide extract can provide better quality duck eggs and can increase panelist preference in egg yolks, egg flavor and egg aroma. In general, the 15 minute soaking time gives the quality of egg yolks, egg flavor and good egg aroma to duck eggs.   Keywords: gelatin, soaking, duck eggs